A numerical estimate of water level elevation due to a cyclone associated with a different landfall angle - Md. Abdul Al Mohit; Md. Towhiduzzaman (SAINS TANAH - Journal of Soil Science and Agroclimatology, 2022)
Bangladesh is a disaster-prone riverine country in South Asia, most of them are cyclone-related. That's why research on cyclones in this region is very important. This study investigates the surge height associated with the changes of landfall angle due to climate change. The deflected angle of landfall was investigated from the data analysis of Bangladesh Meteorological Department (BMD), Joint typhoon warning center (JTWC), and Meteorological Research Institute- Atmospheric global circulation model (MRI-AGCM). A cyclone of future climate has been investigated from the Database for Policy Decision-Making for Future Climate Change (d4PDF) data under present and future climate conditions. To find the surge height, a vertically shallow water Cartesian coordinate model has been used to simulate the surge height. The shallow water model equations were discretized through finite difference technique with the Arakawa C grid system and solved by a conditionally stable semi-implicit manner. The fluctuated striking angle due to climate change was then applied to the known cyclone BOB 01 and the associated surge height was then investigated. We found that our simulated result and the observed result make a good agreement. We have also seen that different types of cyclones have a significant effect on the water level elevation due to their landfall angle